Elevated Skin pH Is Associated With an Increased Permeability to Synthetic Urine. Issue 1 (January 2021) - Koudounas, Sofoklis; Bader, Dan L.; Voegeli, David
Abstract : PURPOSE: The aim of this study was to investigate the permeability of the skin following cleansing activities and its susceptibility to synthetic urine penetration. SUBJECTS AND SETTING: Ten healthy volunteers (aged 22-58 years) participated in the study, which was conducted in a university bioengineering laboratory. METHODS: Tape stripping and sodium lauryl sulfate were used to simulate the physical and chemical irritation exacerbated by frequent cleansing activities, respectively. An untreated site also was selected to evaluate responses of intact skin. Synthetic urine was then applied for a period of 2 hours. Measurements of transepidermal water loss and skin pH were taken at baseline and after each challenge. To quantify the permeability of the skin following exposure, desorption curves of transepidermal water loss were measured and skin surface water loss was calculated. RESULTS: Chemically irritated skin, characterized by increased pH (7.34 ± 0.22), demonstrated an increased permeability to urine, as reflected by a significant increase in mean skin surface water loss (46, 209 ± 15, 596 g/m 2 ) compared to both the intact (14, 631 ± 6164 g/m 2 ) and physically irritated (14, 545 ± 4051 g/m 2 ) skin ( P = .005 in both cases). In contrast, the differences between the intact and physically irritated skin were not significant ( P = .88). CONCLUSION: Permeability of the skin to irritants is influenced by the status of the skin and its acid mantle. These highlight the need to reevaluate the frequency of cleansing activities, along with the choice of product in clinical settings, favoring the use of pH-balanced cleansers.